Alternatives for the acquisition of the written code in public school children who have not attended preschool - Salazar Vanegas, Claudia Yamile; Navarro Tenorio, Andrea Marcela; Carreño Dimas, Nayibe Eugenia (Rastros Rostros, 2024)
Working to achieve the acquisition of the written code in children who have not attended preschool at the San Cristóbal School in the north of the city and who are in first grade, do not have the necessary training, became the challenge that drove the development of this formative research, since this is a rigorous process that involves at first knowing the needs of the students and that have repercussions on the conceptualization that each child makes to acquire the written code.